Leveraging Qardh al-Hasan within Islamic Finance: A Conceptual Framework for Advancing Sustainable Development among Early-stage Enterprises - Ibrahim, Abdul Azis; Alenizi, Abdulrahman (Faculty of Islamic Business and Management, 2024)
Early-stage enterprises significantly contribute to economic development through innovation, job creation, and productivity enhancement. However, these enterprises face substantial financial challenges, particularly in securing capital that adheres to ethical and Sharia-compliant principles. This paper investigates the use of Qardh al-Hasan, an altruistic loan concept in Islamic finance, as a strategic tool for supporting sustainable development initiatives within early-stage enterprises. By leveraging Qardh al-Hasan, which embodies social solidarity and economic justice in Islam, the study proposes a conceptual framework to enhance entrepreneurial resilience and sustainable business practices among nascent businesses. Employing a descriptive analysis and a framework-based review, the research explores strategies to optimize Qardh al-Hasan in financing early-stage enterprises, positioning it as an effective mechanism for addressing sustainability challenges. Key findings reveal Qardh al-Hasan’s potential in fostering sustainable development, while highlighting practical challenges such as default risk, management issues, and liquidity requirements. The analysis indicates a deviation of many Islamic financial institutions from the social objectives of Islamic finance, prioritizing economic growth over holistic development. The theoretical implications enhance the understanding of Qardh al-Hasan’s role in achieving economic and social justice, while practical implications advocate for its integration into modern financial systems to support entrepreneurship and reduce social inequality, emphasizing the need for adequate management and supranational support. This paper’s novelty lies in its innovative approach to repositioning Qardh al-Hasan within contemporary Islamic finance, proposing a comprehensive model that addresses both theoretical and practical challenges, thus advancing the sustainable development objectives of Islamic finance by integrating underprivileged segments into the formal economy. Keywords: Sustainable development, Qardh al-Hasan, Islamic finance, early-stage enterprises.